2013
DOI: 10.5617/nordina.653
|View full text |Cite
|
Sign up to set email alerts
|

Perceived learning experiences regarding Education for sustainable development – within Swedish outdoor education traditions

Abstract: This article presents results from a Swedish exploratory study investigating perceptions of the learning experiences related to education for sustainable development (ESD) by students 10-12 years old. A comprehensive questionnaire with both open and closed questions asking for the students' cognitive, emotional, practical, social, and situated learning experiences was developed. The empirical material consists of the responses from 209 students from six schools. The schools were selected to get a variety of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
3
9
1
1
Order By: Relevance
“…This finding is in line with the findings of a previous study that explored perceptions of the learning experiences related to EfS among 10-to 12-year-old children (Manni, Ottander, Sporre, & Parchmann, 2013). Results of a nationwide study that measured sustainability consciousness in compulsory schools showed a positive but small association with eco-certified schools among students in grade six, while the association was negative among students in grade nine (Olsson, Gericke, & Chang Rundgren, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with the findings of a previous study that explored perceptions of the learning experiences related to EfS among 10-to 12-year-old children (Manni, Ottander, Sporre, & Parchmann, 2013). Results of a nationwide study that measured sustainability consciousness in compulsory schools showed a positive but small association with eco-certified schools among students in grade six, while the association was negative among students in grade nine (Olsson, Gericke, & Chang Rundgren, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…(Child # 28) Not only were the children aware of poverty and economic inequality, but they also had ideas about what to do to address those problems. The findings are in line with those of previous studies, where researchers found that children often described their views in relation to people's real-life situations, and their knowledge, emotions and values were often integrated into their expressions of economic, social and environmental issues of sustainability (Alerby, 2000;Manni, Ottander, Sporre, & Parchmann, 2013).…”
Section: Children's Knowledge and Views Of Economic (In)equalities Insupporting
confidence: 91%
“…The results of the Swedish study indicated that schools with an explicit ESD profile (ESD schools) had only a minor impact on the students' sustainability consciousness in grade 6 and even a negative impact on students in grade 9. Similar results were found in another Swedish study, in which young students' perception of issues regarding ESD in "Green outdoor schools", "ESD schools", and "Non-green-profile schools" was explored (Manni, Ottander, Sporre, & Parchmann, 2013). The statistical results indicated some interrelation between students' experienced cognitive, emotional, social, and situated aspects of learning; however, there was no significant difference between students' outcomes in the different types of school.…”
Section: Introductionsupporting
confidence: 78%
“…Olsson et al (2016) concluded that, even though the schools in the study were so-called "ESD schools", they may have operationalized the ESD guidelines differently. Manni et al (2013) attributed their results to a lack of explicit teaching approaches.…”
Section: Introductionmentioning
confidence: 99%